1994
DOI: 10.1038/bjc.1994.208
|View full text |Cite
|
Sign up to set email alerts
|

Production of endothelin-1 and thrombomodulin by human pancreatic cancer cells

Abstract: Summary Analysis of bioactive substances produced by cancer cells is one approach to understanding the biological features of human cancer. One of these bioactive substances is endothelin (ET)-1, a peptide with potent vasoconstrictive activity produced by vascular endothelial cells. We have previously reported the production of ET-1 by several types of human cancer, especially pancreatic cancer cells. To elucidate whether these cancer cells might share biological characteristics with vascular endothelial cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

1996
1996
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 25 publications
1
20
0
2
Order By: Relevance
“…It is also a high affinity 'thrombin receptor', but its role in tumour biology is not yet completely understood. Our finding of detectable levels of expression in a proportion of pancreatic cancer cell lines confirms a recent report [19] in which 11 out of 12 lines contained detectable expression of TM, often with secretion into the culture medium. Increased levels of plasma TM have been found in patients with pancreatic cancer [20].…”
Section: Discussionsupporting
confidence: 79%
“…It is also a high affinity 'thrombin receptor', but its role in tumour biology is not yet completely understood. Our finding of detectable levels of expression in a proportion of pancreatic cancer cell lines confirms a recent report [19] in which 11 out of 12 lines contained detectable expression of TM, often with secretion into the culture medium. Increased levels of plasma TM have been found in patients with pancreatic cancer [20].…”
Section: Discussionsupporting
confidence: 79%
“…Indicated are mean values (±SD) of the total score and the fibrosis score. For comparison, averaged scores of two healthy rats (neither DBTC nor bosentan application) are shown as well receptor axis in pancreatic cancer as well as pancreatic stellate cells [19][20][21][22][23][24]. PSC are the key effector cells in pancreatic fibrosis, a characteristic feature of PC and an important factor with respect to disease progression [2,5,13,14].…”
Section: Discussionmentioning
confidence: 99%
“…Components of the ET-1/ET receptor axis are also frequently expressed in pancreatic cancer cells [23,24]. In a recent study, Bhargava et al showed that LU-302146, a specific antagonist of endothelin receptor type A (ET R A), inhibited the growth of ET R A-positive pancreatic cancer cell lines in vitro and in vivo, and displayed anti-angiogenic effects [24].…”
Section: Introductionmentioning
confidence: 98%
“…Assays VEGF and ET-1 levels were determined by means of ELISA assay (R&D Systems, Inc., Minneapolis, MN, USA) [22,23]. ProET-1 was detected using an assay in the chemiluminescence-coated tube format as described previously (Brahms AG, Henningsdorf Berlin, Germany) [19,24].…”
Section: Patientsmentioning
confidence: 99%